2016
DOI: 10.1016/j.virol.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Novel interactions between the HTLV antisense proteins HBZ and APH-2 and the NFAR protein family: Implications for the HTLV lifecycles

Abstract: The human T-cell leukaemia virus type 1 and type 2 (HTLV-1/HTLV-2) antisense proteins HBZ and APH-2 play key roles in the HTLV lifecycles and persistence in the host. Nuclear Factors Associated with double-stranded RNA (NFAR) proteins NF90/110 function in the lifecycles of several viruses and participate in host innate immunity against infection and oncogenesis. Using GST pulldown and co-immunoprecipitation assays we demonstrate specific novel interactions between HBZ/APH-2 and NF90/110 and characterised the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 91 publications
0
12
0
Order By: Relevance
“…We observed that endogenous HRS localized in the cytoplasm in a granular pattern, which is consistent with previous reports. APH-2, as described previously, displays fluorescence in a speckle-like manner in the cytoplasm and the nucleus (8,16). In Fig.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…We observed that endogenous HRS localized in the cytoplasm in a granular pattern, which is consistent with previous reports. APH-2, as described previously, displays fluorescence in a speckle-like manner in the cytoplasm and the nucleus (8,16). In Fig.…”
Section: Resultsmentioning
confidence: 63%
“…This led to the conclusion that APH-2 may have a protective role in HTLV-2 infection and may contribute to the nonpathogenic nature of HTLV-2. To date, however, few studies have examined interactions between APH-2 and cellular factors (12,15,16).…”
mentioning
confidence: 99%
“…Plasmid constructs. The expression plasmids encoding Flag-HBZ and HIS-Tax1 were previously described (52,53). Plasmids encoding Flag-IRF7 (wild type), Flag-IRF7 aa 1 to 283 (Flag-IRF7 1-283), Flag-IRF7 283-503, and Flag-IRF7 283-466, together with the luciferase reporter plasmids for IFN-␣ and IFN-␤, were gifts from Fanxiu Zhu, Florida State University (54).…”
Section: Figmentioning
confidence: 99%
“…Another potential mechanism for this difference was described by Murphy et al in 2016. HBZ and APH-2 were individually found to interact with NFAR; HBZ interaction with NFAR resulted in decreased Tax-mediated transactivation while APH-2 interaction with NFAR did not [99].…”
Section: Hbz and Aph-2mentioning
confidence: 99%